Hubungan Kualitas dan Kuantitas Antenatal Care dengan Kejadian Stunting pada Anak Berusia 0-59 Bulan di Puskesmas Tambayoli Tahun 2023 - Susanto, Inneke Kusumawati; Susanto, Djap Hadi; Dwiyanti, Friska (Universitas Kristen Krida Wacana, 2026)
The Indonesian government is targeting a reduction in the prevalence of stunting in children under 5 years of age to 14% by 2024. The Ministry of Health is focusing on eleven stunting intervention programs, one of which is antenatal care (ANC) services. Central Sulawesi Province recorded a stunting prevalence of 28.2%, with a coverage of six ANC visits reaching 70.67%. This study aims to analyze the relationship between risk factors for ANC quality and quantity and the incidence of stunting in children aged 0-59 months in the Tambayoli Community Health Center (Puskesmas) working area during 2023. This observational, analytical study with a cross-sectional design used a purposive sampling technique. Data were collected through questionnaires. Data analysis used the Spearman Rank correlation test with a significance level of p<0.05. The study findings indicate a significant association between ANC quality and stunting incidence (p=0.000; OR 11.28; 95%CI 3.74-33.97). Similarly, the quantity of ANC visits was also significantly associated with stunting (p=0.001; OR 5.46; 95%CI 2.02-14.78). There was a significant association between the quality and quantity of ANC visits and the incidence of stunting in children under 5 years of age in the Tambayoli Community Health Center (Puskesmas) work area. This finding supports stunting intervention programs that emphasize optimizing ANC services. Several previous studies have examined the relationship between ANC visits and stunting, but there has been a paradigm shift from the standard minimum of four to six visits.